Aktivitas Antimikroba Sopi Terhadap Bakteri Patogen Salmonella Typhimurium dan Salmonella Enteritidis - Annytha Ina Rohi Detha; Frans Umbu Datta (JURNAL KAJIAN VETERINER, 2019)
Sopi is a traditional drink from East Nusa Tenggara, made through a fermentation process that is derived from palm trees (Borassus flabellifer L.) which also has the potential to be used as an antimicrobial agent. The purpose of this study was to identify the antimicrobial activity of Sopi against pathogenic bacteria. Identification of the antimicrobial activity conducted in two stages, testing the alcohol content and acidity from sopi; and bioassay testing using pathogenic bacteria Salmonella Typhimurium and Salmonella Enteritidis. The results showed that the Sopi has antimicrobial activity against pathogenic bacteria Salmonella Typhimurium and Salmonella Enteritidis. Results of this research may be basic research to the development of Sopi as an antimicrobial agent.